Sistem Informasi Manajemen Klinik H-Deeja Psychology Center Bojonegoro Berbasis Web - Tegar Wahyu Yudha Pratama; Isnaini Qoriatul Fadhilah; Rifqi Naufal Afif; Siti Makrifatus (Politeknik Negeri Jember, 2024)
Current technological developments are crucial role in various needs, such as management activities and providing health information in various health service institutions. The demand for this information, the use of computers and applications in it is needed to support these activities. The H-Deeja Psychology Center Clinic is a psychology clinic that provides therapy and counseling services for pediatric patients to adult patients, where operational activities are still carried out manually from registration to payment. Thus, making the service late, which should be able to provide fast and accurate service. So, to overcome this problem it is necessary to change the system from manual to electronic. Presence of PMK no. 24 of 2022 concerning medical records in article 3, that in every health service facility, especially clinics, it is mandatory to organize electronic medical records. The purpose of this research is to design and build a management information system for the H-Deeja Psychology Center Clinic. The method used is Waterfall. The resulting application is a Web-based management information system for the H-Deeja Psychology Center Bojonegoro which consists of registration, service, payment and reporting systems. The system is in accordance with the functions and usability of each menu using the black box testing method.